DEVELOPMENT OF TOURISM VILLAGES AND STRENGTHENING The Role of Tourism Awareness Groups Based on Heptahelix of Millennials Of Agrotourism Model: New Ideas For The Development Of Pandemic-Era Tourism Villages - Anna Gustina Zainal; Dian Kagungan; Yulia Neta; Rudy Rudy; Helvi Yanfika (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to encourage the acceleration of tourism village development and increase the institutional ability of tourism awareness groups through training and assistance in order to develop the superior potential of agro-tourism-based tourism "kampoeng kopi" Pekon Rigis Jaya, Air Hitam District, West Lampung Regency by involving the role of NGOs and young people/millennials, In addition, this activity involves the participation of local governments, local communities, universities, entrepreneurs/investors, and the media as well as NGOs (The Heptahelix of Millennials of Agrotourism), Government as regulators, Academics as conceptors, Business as investors, Local Community as Operators, Media as promotions and Non-Government Organizations as Educators and the involvement of Millennials/young people as Consumers. The method used: training, mentoring and focus group discussion The location of the Pekon Rigis Jaya activity, Air Hitam District, West Lampung Regency, the participants of this activity were 20 people. The results of this activity are: The increasing institutional capacity of pokdarwis in tourism development in Pekon Rigis Jaya by supporting the superior tourism development program "kampoeng kopi" West Lampung Regency as one of the international tourist destinations, so that the promotion and marketing of the Rigis jaya "kampoeng kopi" Tourism Village will go viral, by inviting YouTubers, celebgrams, travel vlogger, travel blogger, or someone who has 3F (Followers, Fans, Friends) to visit their village. This is included in the digital influencer section which is one of the communication strategies by the Ministry of Tourism